Energy in Growth Accounting and the Aggregation of Capital and Output - Reiner Kümmel; Dietmar Lindenberger (Biophysical Economics and Sustainability, 2020)
We review the physical aggregation of value added and capital in terms of work performance and information processing and its relation to the deflated monetary time series of output and capital. In growth accounting it complements the time series of labor and energy, measured in hours worked per year and kilowatt-hours consumed per year, respectively. This aggregation is the conceptual basis on which those energy-dependent production functions have been constructed that reproduce economic growth of major industrial countries in the 20th century with small residuals and output elasticities that are for energy much larger and for labor much smaller than the cost shares of these factors. Accounting for growth in such a way, which deviates from that of mainstream economics, may serve as a first step towards integrating the First and the Second Law of Thermodynamics into economics.
Keywords: 330; Aggregation; Cost-share theorem; Economic growth; Energy; Entropy; Output elasticities